The Progesterone receptor agonist Nestorone holds back proinflammatory mediators and neuropathology in Wobbler Mouse motoneuron degeneration - Meyer, Maria (2015)
Wobbler mutant mice suffer from progressive motoneuron degeneration and glial cell reactivity in the spinal cord. To prevent development of these abnormalities, we employed Nestorone, a high-affinity progesterone receptor agonist endowed with neuroprotective, promyelinating and anti-inflammatory activities in experimental brain ischemia, preventing neuroinflammation and chemical degeneration. Five-month-old Wobbler mice (wr-/wr-) received s.c. injections of 200μg/day/mouse of Nestorone in vegetable oil or vehicle for 10days. Control NFR/NFR mice (background strain for Wobbler) received vehicle only. Vehicle-treated Wobblers showed typical spinal cord abnormalities, such as vacuolated motoneurons, decreased immunoreactive choline-acetyltransferase, decreased expression of glutamine synthase (GS), increased glial fibrillary acidic protein-positive (GFAP) astrogliosis and curved digits in forelimbs. These cell-specific abnormalities were normalized in Nestorone-treated Wobblers. In addition, vehicle-treated Wobblers showed Iba1+ microgliosis, high expression of the microglial marker CD11b mRNA and up-regulation of the proinflammatory markers TNFα and iNOS mRNAs. In Nestorone-treated Wobblers, Iba1+ microgliosis subsided, whereas CD11b, TNFα and iNOS mRNAs were down-regulated. NFκB mRNA was increased in Wobbler spinal cord and decreased by Nestorone, whereas expression of its inhibitor IκBα was increased in Nestorone-treated Wobblers compared to control mice and vehicle-treated Wobblers. In conclusion, our results showed that Nestorone restraining effects on proinflammatory mediators, microgliosis and astrogliosis may support neurons in their resistance against degenerative processes